Economic sharing of honors: Equal or exclusive? - Bofu Deng; Jiawei Liu; Li Ji (China Journal of Accounting Research, 2020)
The objective of this study is to examine whether and how non-financial performances, specifically the awards achieved by the corporates, are associated with the distribution of the compensation of the managers and other employees within the corporations. Through an investigation of the correlation between corporate awards and compensation, we find that corporate awards as collective honors raise managers' compensation but significantly reduce non-managerial compensation, thus widening the pay gap within the company. Our empirical evidence also shows that these correlations are more significant in state-owned enterprises than non-state-owned enterprises. In addition, our evidence reveals that although corporate awards increase the stickiness of managers' compensation but not that of other employees, the corporate awards can still stimulate better financial performance and market value by motivating both managers and other employees. Our empirical evidence implies that because only managers are responsible for and evaluated by comprehensive corporate performance, the issues of fairness and efficiency are not raised when the economic benefits provided by corporate awards are unequally shared.
Keywords: 650; Corporate awards; Managerial power; Pay gap